Comparative efficacy and safety of acupuncture for adolescent depression: protocol for a systematic review and Bayesian network meta-analysis - Zhang, Jiayu; Wang, Jiafeng; Xiang, Xingyu; Zhang, Na; Zhang, Kaiying; Zhang, Pengcheng; Wen, Hao (Frontiers in Psychiatry, 2025)
BackgroundAdolescents are in a critical stage of development and represent a high-risk population for depression. Various studies have demonstrated the efficacy of acupuncture therapies in the treatment of adolescent depression. However, trials directly comparing the efficacy and safety of different acupuncture therapies for adolescent depression are still lacking. To identify the optimal acupuncture therapy for treating adolescent depression, we will conduct a systematic review and network meta-analysis of various acupuncture therapies for adolescent depression.MethodsRandomized controlled trials (RCTs) investigating the efficacy and safety of acupuncture in adolescent depression will be systematically searched across the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, Web of Science, and the China National Knowledge Infrastructure (CNKI) databases from inception to December 2025. Study quality will be assessed using the Cochrane Risk of Bias Tool (RoB 2.0), while the Confidence in Network Meta-Analysis (CINeMA) framework will evaluate evidence certainty. The primary outcomes will be included at least one validated depression rating scale for adolescent. Secondary endpoints include safety outcomes, measured by the incidence of adverse events during the study period. Bayesian network meta-analysis will be performed using the gemtc package (v0.8-7) in R statistical software (version 4.0.5).DiscussionThis study will clarify the comparative efficacy and safety of acupuncture for adolescent depression, guiding clinical decision-making.Prospero Registration Numberidentifier (CRD 42024581768).